2018
DOI: 10.1165/rcmb.2016-0344oc
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Anoctamin-1 Limits Pulmonary Endothelial Cell Proliferation via p38–Mitogen-activated Protein Kinase–Dependent Apoptosis

Abstract: Hyperproliferative endothelial cells (ECs) play an important role in the pathogenesis of pulmonary arterial hypertension (PAH). Anoctamin (Ano)-1, a calcium-activated chloride channel, can regulate cell proliferation and cell cycle in multiple cell types. However, the expression and function of Ano1 in the pulmonary endothelium is unknown. We examined whether Ano1 was expressed in pulmonary ECs and if altering Ano1 activity would affect EC survival. Expression and localization of Ano1 in rat lung microvascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 28 publications
(39 reference statements)
2
40
0
Order By: Relevance
“…In our study, we investigated the mechanism of action of Eact, a putative activator of the TMEM16A chloride channel. Eact, which was initially discovered by its high efficacy in FRT cells expressing TMEM16A (Namkung et al 2011b), has been used in many studies to demonstrate the role of TMEM16A in transepithelial ion transport, smooth muscle contraction, endocrine function, mucus release and cell proliferation and migration (Namkung et al 2011b;Berglund et al 2014;Sun et al 2014;Allawzi et al 2018;Song et al 2018;Benedetto et al 2019). In contrast with Eact being a direct activator of TMEM16A, we found little effect of this compound in bronchial epithelial cells under conditions of high TMEM16A expression, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we investigated the mechanism of action of Eact, a putative activator of the TMEM16A chloride channel. Eact, which was initially discovered by its high efficacy in FRT cells expressing TMEM16A (Namkung et al 2011b), has been used in many studies to demonstrate the role of TMEM16A in transepithelial ion transport, smooth muscle contraction, endocrine function, mucus release and cell proliferation and migration (Namkung et al 2011b;Berglund et al 2014;Sun et al 2014;Allawzi et al 2018;Song et al 2018;Benedetto et al 2019). In contrast with Eact being a direct activator of TMEM16A, we found little effect of this compound in bronchial epithelial cells under conditions of high TMEM16A expression, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the protein level and the activity of TMEM16A negatively correlate with VSMC proliferation (Wang et al ., ; Zhang et al ., ), but these correlations were found to be positive in epithelial cells (Ruffin et al ., ; Buchholz et al ., ; Cha et al ., ) and tumour cells (Britschgi et al ., ; Deng et al ., ). Unlike the role of TMEM16A in cell proliferation, which has been fully explored in various cell types, the effect of TMEM16A on cell apoptosis has only been reported for tumour cells (Britschgi et al ., ; Berglund et al ., ; Seo et al ., ; Deng et al ., ) and ECs (Allawzi et al ., ). In this study, we provided evidence that TMEM16A contributes to VSMC apoptosis, and the results were also opposite to those of tumour cells.…”
Section: Discussionmentioning
confidence: 97%
“…In this study, we used immunoblotting and immunogold staining to prove the presence of endogenous TMEM16A expression in mitochondria. This result is consistent with a previous study in endothelial cells (Allawzi et al ., ). Moreover, we explored the intrinsic mechanism of TMEM16A on mitochondrial function.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that TMEM16A is expressed in various smooth muscle cells, such as hypertensive rat basilar smooth muscle cells, pulmonary artery smooth muscle cells (Allawzi et al, ; Davis et al, ; M. Wang et al, ). Indeed, TMEM16A expression and activity were confirmed in smooth muscle cells from various arteries and veins (U. Oh & Jung, ).…”
Section: Tmem16a and Hypertensionmentioning
confidence: 99%